State and fiscal matters in Costa Rica: perceptions of the costa rican population - Sura-Fonseca, Rebeca (2018)
During the last two Costa Rican governments discussions on fiscal matters have occupied an important part of the national agenda. This paper analyzes Costa Rican perceptions about the government use and management of taxes by an exploratory factor analysis and non-hierarchical cluster analysis to a module of eight questions from the fourth survey on tax reform in Costa Rica, Carried out by the CIEP of the UCR, during September of 2016. At the end, it is concluded that there are four discursive nucleus in which Costa Ricans identify themselves: "Taxes serve and the State has a moderate performance in tax matters" (27.1%), "Taxes serve but the State cannot (21.0%), "Taxes serve but the State makes poor management" (38.3%), and "Taxes do not serve and the State also does poor management" (13.6%).